Refinement of the subunit interaction network within the nucleosome remodelling and deacetylase (NuRD) complex. (13th November 2017) - Torrado, Mario; Low, Jason K. K.; Silva, Ana P. G.; Schmidberger, Jason W.; Sana, Maryam; Sharifi Tabar, Mehdi; Isilak, Musa E.; Winning, Courtney S.; Kwong, Cherry; Bedward, Max J.; Sperlazza, Mary J.; Williams, David C.; et al.
Abstract : The nucleosome remodelling and deacetylase (NuRD) complex is essential for the development of complex animals. NuRD has roles in regulating gene expression and repairing damaged DNA. The complex comprises at least six proteins with two or more paralogues of each protein routinely identified when the complex is purified from cell extracts. To understand the structure and function of NuRD, a map of direct subunit interactions is needed. Dozens of published studies have attempted to define direct inter‐subunit connectivities. We propose that conclusions reported in many such studies are in fact ambiguous for one of several reasons. First, the expression of many NuRD subunits in bacteria is unlikely to lead to folded, active protein. Second, interaction studies carried out in cells that contain endogenous NuRD complex can lead to false positives through bridging of target proteins by endogenous components. Combining existing information on NuRD structure with a protocol designed to minimize false positives, we report a conservative and robust interaction map for the NuRD complex. We also suggest a 3D model of the complex that brings together the existing data on the complex. The issues and strategies discussed herein are also applicable to the analysis of a wide range of multi‐subunit complexes. Enzymes: Micrococcal nuclease (MNase), EC 3.1.31.1 ; histone deacetylase (HDAC), EC 3.5.1.98 . Abstract : The nucleosome remodelling and deacetylase (NuRD) complex is essential for gene regulation in complex animals. To understand its structure, a map of direct subunit interactions is needed. We assessed the reliability of published data on this area and experimentally mapped interactions to develop a high‐confidence interaction map of the NuRD complex.